Political empowerment in the Prophet’s experience through the Treaty of Ḥudaybiyyah = التمكين السياسي في تجربة النبي صلى الله عليه وسلم من خلال صلح الحديبة - Ahmed, Maryam Dawood; Gasmelsid, Saadeldin Mansour (IIUM Press, 2023)
This research deals with an analytical reading of the political empowerment in the experience of the Prophet PBUH, through the Treaty of Hudaybiyyah (Ṣulḥ al-Ḥudaybiyyah). It reveals the dimensions of the political empowerment brought about by the Messenger PBUH, and from it the empowerment of God’s religion is accomplished on earth, the realization of the purpose of man’s existence in this universe, and the liberation of people from worshiping people to worshiping the God, and these major goals we see achieved in the context of this type of political empowerment. The Qur’an has dealt with this subject in all its aspects, which confirms its vital role in the reality of the nation, and monitors the nature of this concept, its conditions, its objectives, and its different levels. This research adopts an inductive and analytical approach to clarify the theoretical dimension of the concept of political empowerment, and to address the practical aspects related to it by reviewing its images in some of the prophetic experiences in order to establish the foundations of the right in human reality, and to build a civilized awareness that elevates nations to the ultimate worship goal.